Role of aneuploidy screening in preimplantation genetic testing for monogenic diseases in young women - Hou, Wenhui; Xu, Yan; Li, Rong; Song, Junli; Wang, Jing; Zeng, Yanhong; Pan, Jiafu; Zhou, Canquan; Xu, Yanwen (Fertility and sterility, 2019)
To investigate whether aneuploidy screening in preimplantation genetic testing (PGT) for monogenic diseases improves the ongoing pregnancy/live birth rate of single frozen/thawed embryo transfer (FET) cycles in young women. Retrospective cohort study. Single university-based fertility center. From January 2016 to December 2017, 569 FET cycles were selected for analysis. The aneuploidy screening (AS) group included 131 FET cycles from 105 oocyte retrieval cycles in 98 patients who underwent PGT for monogenic diseases with aneuploidy screening, and the non-AS group included 438 FET cycles from 280 oocyte retrieval cycles in 266 patients who underwent PGT for monogenic diseases without aneuploidy screening. The patient population was all under the age of 35 years and underwent PGT for monogenic diseases with and without AS. Ongoing pregnancy/live birth rate, live birth rate, implantation rate, and miscarriage rate. Aneuploidy screening significantly improved the ongoing pregnancy/live birth rate (61.22% vs. 43.98%), implantation rate (64.29% vs. 50.38%), and live birth rate (53.06% vs. 36.09%) of young women carrying monogenic diseases in the first FET cycles. When adjusted for the parity, number of previous miscarriages, and percentage of infertility, the likelihood of implantation was 1.874 times higher (95% confidence interval 1.126–3.119), and an ongoing pregnancy/live birth was 2.139 times more likely (95% confidence interval 1.295–3.534). In addition, the miscarriage rate was significantly decreased (3.17% vs. 11.94%). In the cumulative pregnancy outcomes, the cumulative ongoing pregnancy/live birth rate both per transfer and per patient were significantly higher in the AS group (62.24% vs. 50.38% and 79.59% vs. 68.80%), but no difference existed after adjusting for the parity, number of previous miscarriage, and percentage of infertility. Nevertheless, aneuploidy screening reduced the time interval from the first ET to the achievement a pregnancy. Aneuploidy screening in PGT significantly improved the ongoing pregnancy/live birth rate of young women carrying monogenic diseases in the first FET cycles. Papel del cribado de aneuploidías en test genético preimplantacional para enfermedades monogénicas en mujeres jóvenes Investigar si el cribado de aneuploidías en el test genético preimplantacional (PGT) para enfermedades monogénicas mejora la tasa de embarazo evolutivo/nacido vivo de ciclos de transferencia de embrión único congelado (FET) en mujeres jóvenes. Estudio retrospectivo de cohortes. Centro único de fertilidad universitario. Desde Enero de 2016 a Diciembre de 2017, 569 ciclos de FET fueron seleccionados para el análisis. El grupo de cribado de aneuploidías (AS) incluyó 131 ciclos de FET de 105 ciclos de recuperación ovocitaria en 98 pacientes que realizaron PGT para enfermedades monogénicas con cribado de aneuploidías, y el grupo de no-AS incluyó 438 ciclos de FET de 280 ciclos de recuperación ovocitaria en 266 pacientes que realizaron PGT para enfermedades monogénicas sin cribado de aneuploidías. La población de pacientes estuvo toda por debajo de los 35 años y realizó PGT para enfermedades monogénicas con y sin AS. Tasa de embarazo evolutivo/nacido vivo, tasa de nacido vivo, tasa de implantación, y tasa de aborto. El cribado de aneuploidías mejoró significativamente la tasa de embarazo evolutivo/nacido vivo (61,22% vs. 43,98%), tasa de implantación (64,29% vs. 50,38%), y tasa de nacido vivo (53,06% vs. 36,09%) de mujeres jóvenes portadoras de enfermedades monogénicas en el primer ciclo de FET. Cuando se ajustó por la paridad, número de abortos previos, y porcentaje de infertilidad, la probabilidad de implantación fue 1,874 veces más alta (intervalo de confianza 95% 1,126-3,119), y embarazo evolutivo/nacido vivo fue 2,139 veces más probable (intervalo de confianza 95% 1,295-3,534). Además, la tasa de aborto fue disminuida significativamente (3,17% vs. 11,94%). En los resultados gestacionales acumulativos, la tasa acumulativa de embarazo evolutivo/nacido vivo tanto por transferencia y por paciente fueron significativamente más altas en el grupo AS (62,24% vs. 50,38% y 79,59% vs. 68,80%), pero no existió diferencia después de ajustar según paridad, número de abortos previos, y porcentaje de infertilidad. Sin embargo, el cribado de aneuploidías redujo el intervalo de tiempo desde el primer ET hasta lograr un embarazo. Cribado de aneuploidías en PGT mejoró significativamente la tasa de embarazo evolutivo/nacido vivo de mujeres jóvenes portadoras de enfermedades monogénicas en el primer ciclo de FET.